Clay mineral evidence for sediment provenance and the evolution of the East Asian Winter Monsoon in the central Philippine Sea over the last 4.38 Ma - Jun Sun; Fei Guo; Huaichun Wu; Wei Huang; Jian Liu; Kai Lu; Jingfang Lu; Shuang Sun; Meinan Shi; Boya Li; Liwei Liu; Xiaoke Qiang (Global and Planetary Change, 2026)

Carbon-confinement modulated interfacial water structure for accelerated dissociation kinetics towards hydrogen evolution - Fanpeng Cheng; Yue Yu; Yulu Wan; Dashuai Wang; Shangqing Chen; Jingfang Zhang; Huijuan Guo; Yang Xia; Yi Huang; Lijuan Shi; Liwei Cheng; Qun Yi (Chemical Engineering Journal, 2025)

Acetylcholinesterase-free colorimetric sensing platform for carbosulfan detection based on hollow PDA/MnO2 nanozyme - Jingfang Guo; Feng Zhao; Zhenhui Yue; Zhen Lei (Food Chemistry, 2025)

CeO2 nanocages with tetra-enzyme mimetic activities for dual-channel ratiometric colorimetric detection of microcystins-LR - Guodong Wang; Jingfang Guo; Jing Zou; Zhen Lei (Analytica Chimica Acta, 2024)

Enhanced AGS by granular activated carbon loaded with nano iron when treating low strength and low COD/TN ratio municipal wastewater: Microbial metabolism, electron transfer and enhancement mechanism - Lei Peng; Haibo Li; Jianbo Guo; Jingfang Lu; Yanan Hou; Yi Han; Daohong Zhang; Yuanyuan Song; Jianhai Zhao (Journal of Environmental Chemical Engineering, 2024)

PBX1-promoted SFRP4 transcription inhibits cell proliferation and epithelial-mesenchymal transition in endometrial carcinoma - Liwen Guo; Huihua Chen; Jinguo Chen; Chen Gao; Xianguo Fu; Sujuan Zhou; Wenjuan Wu; Taoping Li; Jingfang Lin; Tailai Yang; Zichun Chen; Luoyuan Cao (Tissue and Cell, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

The neglected potential source of microplastics from daily necessities: A study on protective mobile phone cases - Qilu Li; Meng Yuan; Yuan Chen; Xinjie Jin; Jingfang Shangguan; Jinle Cui; Shixiang Chang; Mengran Guo; Yan Wang (Journal of Hazardous Materials, 2023)

Streptococcus humanilactis sp.nov., isolated from healthy nursing mother's breast milk - Xiaoqing Guo; Fei Han; Lin Cong; Yu Li; Yue Wu; Chen Liu; Jingfang Yang; Risu Na; Wenjun Liu (Archives of Microbiology, 2022)

The crosstalk between the Notch, Wnt, and SHH signaling pathways in regulating the proliferation and regeneration of sensory progenitor cells in the mouse cochlea - Jingfang Wu; Wen Li; Luo Guo; Liping Zhao; Shan Sun; Huawei Li (Cell and Tissue Research, 2021)
Sensory hair cells (HCs) are highly susceptible to damage by noise, ototoxic drugs, and aging. Although HCs cannot be spontaneously regenerated in adult mammals, previous studies have shown that signaling pathways are involved in HC regeneration in the damaged mouse cochlea. Here, we used a Notch antagonist (DAPT), a Wnt agonist (QS11), and recombinant Sonic hedgehog (SHH) protein to investigate their concerted actions underlying HC regeneration in the mouse cochlea after neomycin-induced damage both in vivo and in vitro. With DAPT, the numbers of HCs increased, and supporting cell (SC) proliferation was seen in both the intact and damaged cochlear sensory epithelia, while these numbers were unchanged in the presence of QS11. When simultaneously treated with DAPT and QS11, the number of HCs increased dramatically, and much greater SC proliferation was seen in the cochlear epithelium. In transgenic mice with both Notch1 conditional knockout and β-catenin over-expression, cochlear SC proliferation and HC regeneration were more obvious than in either Notch1 knockout or β-catenin over-expressing mice separately. When cochleae were treated with DAPT, QS11, and SHH together, SC proliferation was even greater, and this proliferation was seen in both the HC region and the greater epithelial ridge. High-throughput RNA sequencing was used to identify the differentially expressed genes between all groups, and the results showed that the SHH and Wnt signaling pathways are involved in SC proliferation. Our study suggests that co-regulation of the Notch, Wnt, and SHH signaling pathways promotes extensive cell proliferation and regeneration in the mouse cochlea.

Complete genome sequence of a novel lytic bacteriophage isolated from Ralstonia solanacearum - Jingfang Su; Hongwei Sun; Junjie Liu; Zhaokui Guo; Guoquan Fan; Gang Gu; Guanghua Wang (Archives of Virology, 2017)